Solvent-free Synthesis of Transition Metals Nanoparticles Decorated Foamy Flakes-like Nitrogen-doped Carbon as Bifunctional-catalyst for High-performance Rechargeable Zn-air Batteries - Persada, Pilar Bela; Tan, Davin Adinata; Akmalia, Rachendra; Irmawati, Yuyun; Sumboja, Afriyanti (Journal of Engineering and Technological Sciences, 2023)
Transition metal-nitrogen-carbon (M/NC) demonstrates a promising effective electrocatalyst for enhancing oxygen evolution/reduction reactions (OER/ORR). However, synthesizing these catalysts is often complex, time-consuming, and involves hazardous solvents while producing a low yield. This work introduces a versatile, eco-friendly, and straightforward solvent-free method to produce M/NC (M = Co, Ni, and Fe) catalysts in 3 h using a glucose, urea, and metal nitrate hydrate mixture. The high-yield M/NC catalysts exhibit a porous architecture and uniform distribution of metal nanoparticles within a foaming flakes-like nitrogen-doped carbon matrix. The metal nanoparticles are wrapped with protective nitrogen-doped carbon layers, producing stable active sites. Possessing these unique properties, the obtained M/NC catalysts show high-performance and stable bifunctional OER/ORR. As the best result, Co/NC presents an OER/ORR potential difference (ΔE) of 0.78 V and retains 96% and 89% of its OER and ORR performance after a 10 h stability test. In practical application, the Co/NC-based Zn-air battery depicts a high power density of 184 mW cm−2 and good rechargeability of up to 120 h, outperforming the battery with noble metal-based catalysts. This work sheds light on the versatile, eco-friendly, and scalable synthesis of M/NC catalysts while presenting a strategy to accelerate the generation of inexpensive and highly effective bifunctional OER/ORR catalysts.